![image](https://tex.z-dn.net/?f=%3D%5Cfrac%7B3%2B2log_23%7D%7B3%2Blog_23%7D%3D%5Cfrac%7B3%2B2t%7D%7B2%2Bt%7D%2C%5C%3B+t%3Dlog_23%3E0%2C%5C%3B+%28t.k.%5C%3B+3%3E2%2Ca%5C%3B+log_22%3D1%29%5C%5C%5C%5Clog_%7B12%7D%7B18%7D%3D%5Cfrac%7Blog_2%7B18%7D%7D%7Blog_2%7B12%7D%7D%3D%5Cfrac%7Blog_2%7B%283%5E2%5Ccdot+2%29%7D%7D%7Blog_2%7B%282%5E2%5Ccdot+3%29%7D%7D%3D%5Cfrac%7B1%2B2log_23%7D%7B2%2Blog_23%7D%3D%5Cfrac%7B1%2B2t%7D%7B2%2Bt%7D%2C%5C%3B+t%3Dlog_23%3E0%5C%5C%5C%5Clog_%7B24%7D%7B72%7D-log_%7B12%7D%7B18%7D%3D%5Cfrac%7B3%2B2t%7D%7B3%2Bt%7D-%5Cfrac%7B1%2B2t%7D%7B2%2Bt%7D%3D%5Cfrac%7B3%7D%7B%283%2Bt%29%282%2Bt%29%7D%3E0%5C%3B+%5C%3B+%5Cto+%5C%3B+%5C%3B+%5C%5C%5C%5Clog_%7B24%7D%7B72%7D%3Elog_%7B12%7D%7B18%7D)
0,\; (t.k.\; 3>2,a\; log_22=1)\\\\log_{12}{18}=\frac{log_2{18}}{log_2{12}}=\frac{log_2{(3^2\cdot 2)}}{log_2{(2^2\cdot 3)}}=\frac{1+2log_23}{2+log_23}=\frac{1+2t}{2+t},\; t=log_23>0\\\\log_{24}{72}-log_{12}{18}=\frac{3+2t}{3+t}-\frac{1+2t}{2+t}=\frac{3}{(3+t)(2+t)}>0\; \; \to \; \; \\\\log_{24}{72}>log_{12}{18}" alt="=\frac{3+2log_23}{3+log_23}=\frac{3+2t}{2+t},\; t=log_23>0,\; (t.k.\; 3>2,a\; log_22=1)\\\\log_{12}{18}=\frac{log_2{18}}{log_2{12}}=\frac{log_2{(3^2\cdot 2)}}{log_2{(2^2\cdot 3)}}=\frac{1+2log_23}{2+log_23}=\frac{1+2t}{2+t},\; t=log_23>0\\\\log_{24}{72}-log_{12}{18}=\frac{3+2t}{3+t}-\frac{1+2t}{2+t}=\frac{3}{(3+t)(2+t)}>0\; \; \to \; \; \\\\log_{24}{72}>log_{12}{18}" align="absmiddle" class="latex-formula">